Study on swelling behaviour of HANP/PVA composites with adding PLGA for alveolar ridge preservation - Feni Istikharoh; Hidayat Sujuti; Edi Mustamsir; Astika Swastirani (DiscoverSys Inc., 2021)
Objective: The aim of this study was to compare the swelling behaviour of Hand Polyvinyl Acetate/Polyvinyl alcohol (HANP/PVA) and HANP/PVA/Poly Lactic-co-Glycolic Acid (PLGA) composites.Material and Methods: This study was divided into 2 groups, HANP/PVA and HANP/PLGA/PVA composites which prepared by freeze drying methods. HANP 20% (w/w) was combined with PLGA 20% (w/w) and dissolved in PVA solution at 50oC. Swelling behaviour was obtained by measured initial weight (Wi) and the weight of composites after immersing in PBS pH 7.4; 37oC for 7 days (swollen weight (Ws)). Statistical analysis based on Independent T-test (p<0.05).Results: The Wi of HANP/PVA and HANP/PLGA/PVA composites are 467±4.73 and 292±9.52. The Ws of HANP/PVA and HANP/PLGA/PVA composites are 897±26.61 and 860±32.36. Furthermore, the water retention of HANP/PVA composite is 92.07% (p<0.05) and HANP/PLGA/PVA composite is 194.52% (p<0.05).Conclusion: The addition of PLGA enhance swelling behaviour of HANP/PVA composites. The strong interaction between HANP and PVA decrease the swelling re. HANP is inert in nature, but the combination of HANP/PLGA/PVA can be a good substitute for alveolar preservation.